2020
DOI: 10.3389/fpls.2020.568009
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphological Traits of Seedlings Are Predictors of Seed Yield and Quality in Winter Oilseed Rape Hybrid Cultivars

Abstract: The root system is responsible for soil resources acquisition. Hence, optimizing crop root characteristics has considerable implications for agricultural production. This study evaluated a panel of twenty-eight European modern cultivars of oilseed rape (Brassica napus L.) cultivated in laboratory and field environments. Root morphology was screened using a high-throughput hydroponic growth system with two divergent nitrogen supplies. The panel showed an important diversity for biomass production and root morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
(97 reference statements)
1
20
0
Order By: Relevance
“…Nevertheless, the testing under eld condition could result an increased underestimation of root architectural parameters, therefore we complemented the eld trial with a hydroponic experiment, where the entire root system morphology could be estimated. As already shown in root morphological trials in Brassica, the root development in seedling stage is a reliable indicator for the following development stages 37 . We hypothesized that this is also true in barley.…”
Section: Discussionmentioning
confidence: 56%
“…Nevertheless, the testing under eld condition could result an increased underestimation of root architectural parameters, therefore we complemented the eld trial with a hydroponic experiment, where the entire root system morphology could be estimated. As already shown in root morphological trials in Brassica, the root development in seedling stage is a reliable indicator for the following development stages 37 . We hypothesized that this is also true in barley.…”
Section: Discussionmentioning
confidence: 56%
“…To test parental lines of studied populations, 89 SSR primer pairs were used. Some of these primers were also tested in rapeseed genetic diversity studies [17,19,46,47]. After initial analysis, 43 markers proved to be polymorphic and were used to analyze all genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the results of Malagoli et al ( 2005a ), who reported a loss of 12% of plant N in fallen leaves. Some other studies assessing NUE include tap roots and sometimes fine roots, but not fully for each individual plant (Ulas et al, 2012 ; Hohmann et al, 2016 ; Yuan et al, 2016 , Dresbøll et al, 2016 ) or at each phenological stage, mainly targeting either the seedling or reproductive stages (Thomas et al, 2016 ; Wang et al, 2017 ; Louvieaux et al, 2020 ). To our knowledge, our study is the first to describe the NUE dynamics of winter oilseed rape so completely and accurately, by considering entire individual plants grown under canopy conditions at key phenological stages from sowing to seed maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a genotypic analysis of the fine-root growth, seen as a proxy of root architecture, could provide some clues of NUE determinism. Indeed, Wang et al ( 2017 ) highlighted a strong correlation between root biomass and total root area on young plants of winter oilseed rape, and Louvieaux et al ( 2020 ) evidenced a positive correlation between primary root length early measured in hydroponics and seed yield measured in the field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation